Research hotspots and trends in the application of electroencephalography for assessment of disorders of consciousness: a bibliometric analysis - Chen, Jiawen; Shi, Yanhua; Dong, Zhao; Xu, Feng; Zhou, Mengyu; Zhu, Jing; Gao, Jie; Liu, Su (Frontiers in Neurology, 2025)
ObjectiveDisorders of consciousness (DoC) result from severe traumatic brain injury and hypoxia or ischemia of brain tissues, leading to impaired perceptual abilities. Electroencephalography (EEG) is a non-invasive and widely applicable technology used for assessing DoC. We aimed to identify the research hotspots in this field through a systematic analysis.MethodsRelevant studies published from January 1, 2004 to December 31, 2023 were retrieved from the Web of Science Core Collection database. The data were analyzed and visualized using CiteSpace, VOSviewer, and SCImago Graphica.ResultsIn total, 1,639 relevant publications were retrieved. The country with the highest number of publications was the United States, the most productive institution was Harvard University, the journal with the highest output was Clinical Neurophysiology, and the journal with the highest total number of citations was Neurology. The author with the most publications was Steven Laureys and the most common keyword was “vegetative state.”ConclusionThe field is undergoing rapid development, characterized by a proliferation of advanced technologies and an increased emphasis on international collaboration. The document offers an impartial perspective on the advancements of the research study for the benefit of the researchers.